2014
DOI: 10.1080/07347332.2014.955243
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Positive Health Behaviors in Cancer Survivors: Results from the 2010 LIVESTRONG Survey

Abstract: Positive health-promoting behaviors, including lifestyle factors (e.g., physical activity) and appropriate health service utilization (e.g., screening for secondary cancers), can minimize the health risks and challenges facing cancer survivors. The goal of this article is to examine factors associated with positive health behaviors in 2,615 posttreatment cancer survivors who completed the 2010 LIVESTRONG survey. Multivariate logistic regression was used to model odds of reporting each of six positive health be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
0
30
1
2
Order By: Relevance
“…W długoterminowej opiece nad chorymi na nowotwór niezbędne jest podejście wielodyscyplinarne [257]. W przeglądzie 56 prób klinicznych obejmujących 4826 osób wykazano poprawę jakości życia i sprawności fizycznej podczas programu treningu wysiłkowego i po jego zakończeniu (tab.…”
Section: Interwencje Niefarmakologiczne O Działaniu Kardioprotekcyjnyunclassified
“…W długoterminowej opiece nad chorymi na nowotwór niezbędne jest podejście wielodyscyplinarne [257]. W przeglądzie 56 prób klinicznych obejmujących 4826 osób wykazano poprawę jakości życia i sprawności fizycznej podczas programu treningu wysiłkowego i po jego zakończeniu (tab.…”
Section: Interwencje Niefarmakologiczne O Działaniu Kardioprotekcyjnyunclassified
“…20 Among NSCLC survivors, increasing age and the presence of pulmonary conditions were associated with lower odds of PSA screening. 20 Four studies focused specifically on adherence to surveillance guidelines after treatment for colorectal cancer, 21-24 defined as ≥2 office visits in the first 3 years (applicable for stages I-III), and ≥1 colonoscopy since surgical resection (applicable for stages I-III), and at least 1 computed tomography scan since surgical resection (applicable for stages II-III). 19 In the study of survivors with multitumor types, a greater number of years from cancer diagnosis was associated with lower odds of attending all medical appointments (OR, 0.39) and being up-to-date on screenings (OR, 0.79).…”
Section: Guideline-adherence Visitsmentioning
confidence: 98%
“…[19][20][21][22][23][24] Two survey-based studies of cancer survivors indicated high self-reported rates of adherence to routine primary care visits in the past year (97% in a nonsmall cell lung cancer [NSCLC] population 19 and 92% in a sample with multitumor types 20 ). [19][20][21][22][23][24] Two survey-based studies of cancer survivors indicated high self-reported rates of adherence to routine primary care visits in the past year (97% in a nonsmall cell lung cancer [NSCLC] population 19 and 92% in a sample with multitumor types 20 ).…”
Section: Guideline-adherence Visitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have suggested that a cancer diagnosis itself may serve as a stimulus for survivors to make the behavioral changes supported by such guidelines [2], a notion supported by several studies among cancer survivors [1115]. However, existing studies of health behaviors after a breast cancer diagnosis are most often conducted within samples of women who are recruited and enrolled after diagnosis.…”
Section: Introductionmentioning
confidence: 99%